Analisis Permasalahan Outsourcing dari Perspektif Hukum dan Penerapannya - Khairani Khairani (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: Outsourcing is a matter worded in the Labour Act and the latest issue in relation to Indonesia labour. It is ruled in terms of easing employers to manage the company in providing the labour service. The implementation is regulated strictly in Article 64-66 of the Act Number 13, 2003 regarding the Labour. However, in the implementation level the violation is unavoidable causing the trouble. It happens as the outsourcing is defect both the legislation and its implementation. Outsourcing Analysis Problem from the Perspective of Law and Implementation